De novo transcriptome assembly and annotation of the semi-wild Gayal (Bos frontalis) - Zhendong Gao; Bo Wang; Ying Lu; Yuqing Chong; Mengfei Li; Jieyun Hong; Jiao Wu; Dongmei Xi; Weidong Deng (Scientific Data)
Abstract The Gayal (Bos frontalis) is a rare semi-wild Bovine species that inhabits the harsh environments of Indo-China. Although the origins of the Gayal remain largely enigmatic, addressing the lack of comprehensive transcriptomic data is critical for understanding its genetic and molecular characteristics, which are essential for formulating effective conservation and management plans. In this study, an integrated PacBio Iso-seq and RNA-seq analysis was conducted on samples from 10 different organs and tissues of the Gayal, with each being sequenced in triplicate. The samples analyzed included the heart, liver, spleen, lung, kidney, rumen, abomasum, duodenum, ileum, and rectum. This comprehensive analysis resulted in the identification of 30,760 full-length transcripts ranging from 363 bp to 7,157 bp, with transcript information matched to seven commonly used databases. Gene family clustering and phylogenetic analyses encompassed a comprehensive dataset of 9 Bovine species, including the Gayal. Additionally, long non-coding RNAs (lncRNAs) were identified across all sampled tissues, and comprehensive gene expression profiles and differential expression gene analyses were performed. These findings provide a rich repository of genetic information, laying the foundation for comprehensive functional genomics studies and paving the way for deeper insights into the molecular mechanisms of the Gayal, thereby advancing our understanding of its transcriptome architecture and offering crucial data for conservation efforts and practical applications.